ARSIP KARYA SENI DAN KARAKTERISTIKNYA - Nurhalifah; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Art work archives are records that document the creative process, presentation, and utilization of artistic works, holding informational, historical, cultural, and aesthetic value. This study aims to explain the concept, types, characteristics, and significance of art work archives through a descriptive qualitative literature review. The results show that art work archives can be classified into fine art archives, performing art archives, music archives, audiovisual archives, and digital art archives. These archives possess distinctive characteristics, including uniqueness, aesthetic value, historical and cultural significance, diverse forms and media, the need for special preservation, and long-term usability. Art work archives play an important role in preserving collective memory, supporting education and research, and safeguarding cultural heritage. Therefore, sustainable management and preservation of art work archives are essential to maintain their value for present and future generations.